Revitalizing Macapat Songs as Intangible Cultural Heritage: A Study of Values, Functions, and Preservation Challenges in the Digital Era - Kusumardani, Amisha Madu; Werdiningsih, Yuli Kurniati; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
Tembang Macapat is a form of metered Javanese poetry that holds a significant position as a medium for transmitting cultural, spiritual, and social values in Javanese society. In the era of globalization and digitalization, the existence of tembang macapat faces challenges from declining interest among younger generations and the erosion of its social habitus. This study aims to: (1) systematically identify the values embedded in tembang macapat; (2) analyze the functions of tembang macapat within the contemporary Javanese socio-cultural system; and (3) map the challenges and strategies for preserving tembang macapat in the digital age. The method employed is a systematic literature review with a qualitative-descriptive approach and hermeneutic analysis of relevant primary and secondary sources. Data were collected through examination of manuscripts, journal articles, and cultural policy documents published between 2019 and 2024. The findings reveal that tembang macapat contains three main layers of values: philosophical-spiritual, moral, and social values that are interrelated. Functionally, tembang macapat serves as a medium for religious propagation, character education, and social cohesion. The main challenges to preservation include low cultural literacy among younger generations, minimal integration into formal curricula, and competition with digital popular culture. Revitalization strategies through digital platforms, cross-genre artistic collaboration, and strengthening local wisdom-based curricula are deemed most relevant and sustainable.